2014
DOI: 10.3390/ma7128131
|View full text |Cite
|
Sign up to set email alerts
|

Properties Characterization of Chemically Modified Hemp Hurds

Abstract: The effect of chemical treatment of hemp hurds slices in three solutions (EDTA (Ethylenediaminetetraacetic acid), NaOH and Ca(OH)2) on the properties of natural material was discussed in this paper. Changes in the morphology, chemical composition and structure as well as thermal stability of hemp hurds before and after their modification were investigated by using FTIR (Fourier transform infrared spectroscopy), XRD (X-ray powder diffraction analysis) and TG (thermogravimetry)/DSC (differential scanning calorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
95
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(113 citation statements)
references
References 43 publications
13
95
2
3
Order By: Relevance
“…This is accordance with [11], where chemical modification of hemp hurds led to cleaning the surface repulped of hurds slices and improvement of the adhesion between the fibers and inorganic matrix. The study of hemp hurds properties after alkaline treatment in [5] confirmed changes in defibrillation of bundles, chemical and phase composition, cellulose crystallinity and degree of cellulose polymerization. Compressive strength values of composites increase with increasing hardening time, as shown in Table 2.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This is accordance with [11], where chemical modification of hemp hurds led to cleaning the surface repulped of hurds slices and improvement of the adhesion between the fibers and inorganic matrix. The study of hemp hurds properties after alkaline treatment in [5] confirmed changes in defibrillation of bundles, chemical and phase composition, cellulose crystallinity and degree of cellulose polymerization. Compressive strength values of composites increase with increasing hardening time, as shown in Table 2.…”
Section: Resultsmentioning
confidence: 95%
“…The mean particle length of hemp hurds, chemical composition changed by treatment and binder nature as the most important parameters controlling the mechanical properties of composites were investigated [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…7C), and bleaching (Fig. 7D) showed the typical cellulose bands at 899 cm -1 (symmetric stretch, in-plane(C-O-C) of β-(1→4)-glycosidic linkages), indicating that the cellulose structure had few changes during degumming (Stevulova et al 2014). The band at 1730 cm -1 was attributed to the C=O stretching of ester groups and carbonyl in pectin and hemicellulose (Sisti et al 2016).…”
Section: Ft-ir Analysesmentioning
confidence: 98%
“…According to Stevulova et al (2014), peak at wavelength 2800-3400 cm -1 indicates polysaccharides, 1300-1400 cm -1 indicates cellulose, 1028 and 1733 cm -1 shows hemicellulose groups, whereas wavelength 1500-1600 cm -1 shows a lignin group. Figure 2 shows that the standard FTIR spectrum of cellulose and the Figure 2.…”
Section: Characteristics Of Seaweed Processing Wastementioning
confidence: 99%